1982
DOI: 10.1111/j.1467-8624.1982.tb04152.x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of IQ and Language Skill from Perinatal Status, Child Performance, Family Characteristics, and Mother-Infant Interaction

Abstract: 193 basically healthy working-class and middle-class mothers and their infants participated in a 4-year longitudinal study which focused on the relative potency of several clusters of variables for predictions of intellectual and language outcome during the preschool years. The major results were: (1) Measures of perinatal or infant physical status were extremely weak predictors of 4-year IQ or language. (2) Assessments of child performance were poor predictors prior to 24 months, but excellent predictors from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
76
2

Year Published

1986
1986
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 39 publications
7
76
2
Order By: Relevance
“…In another longitudinal study, Bornstein (1986) used path modeling to determine the relative contributions of maternal didactics and found that maternal didactics at 4 months contributed more strongly to productive vocabulary size in l-year-olds than the same maternal didactics at 12 months did to verbal intelligence in 4-year-olds. Similar findings have been published by Olson, Bates & Bayles (1984) as well as Bee, Barnard, Eyres, Gray, Hammond, Spietz, Snyder & Clark (1982).…”
Section: The Infant's Didactical Environmentsupporting
confidence: 80%
“…In another longitudinal study, Bornstein (1986) used path modeling to determine the relative contributions of maternal didactics and found that maternal didactics at 4 months contributed more strongly to productive vocabulary size in l-year-olds than the same maternal didactics at 12 months did to verbal intelligence in 4-year-olds. Similar findings have been published by Olson, Bates & Bayles (1984) as well as Bee, Barnard, Eyres, Gray, Hammond, Spietz, Snyder & Clark (1982).…”
Section: The Infant's Didactical Environmentsupporting
confidence: 80%
“…Parental perceptions are presumed to govern the interactive behaviors of the parent with the infant. Research supports the suggested link between parental perceptions of the newborn's capacities, the consequent expectations derived from these perceptions, and the resulting parenting behaviors (Bee et al, 1982;Stern & Hildebrandt, 1986). We propose that the working model can be influenced postnatally in the newborn period by (1) the parents' capacity to observe their newborn, (2) the meaning that parents ascribe to their observations, and (3) their sensed competence or self-esteem as parents.…”
Section: Theory and Related Researchmentioning
confidence: 82%
“…All four categories -baby's behavior, environment, parent-child interaction, and family stress levelshad separate correlations with developmental outcomes, including cognitive and language measures (Barnard & Eyres, 1979). However, the best predictors were the environment and parent-child interaction (Bee et al, 1982).…”
Section: Parent-child Interactionmentioning
confidence: 99%